Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1540-6210.2012.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Local E‐Government in the United States: Transformation or Incremental Change?

Abstract: In this article, the authors address the recent trajectory of local e‐government in the United States and compare it with the predictions of early e‐government writings, using empirical data from two nationwide surveys of e‐government among American local governments. The authors find that local e‐government has not produced the results that those writings predicted. Instead, its development has largely been incremental, and local e‐government is mainly about delivering information and services online, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
168
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(206 citation statements)
references
References 44 publications
(52 reference statements)
10
168
2
5
Order By: Relevance
“…The above-indicated results are comparable with research findings (i.e., Norris 2005;Norris and Reddick 2013). Based on four focus groups involving a total of 37 IT and other local U.S. government officials, Norris (2005) found that local governments adopted and implemented online services mostly to provide information and e-services and also to provide citizen access to government officials.…”
Section: Figure 3 External Reasons To Undertake E-services Initiativessupporting
confidence: 77%
See 1 more Smart Citation
“…The above-indicated results are comparable with research findings (i.e., Norris 2005;Norris and Reddick 2013). Based on four focus groups involving a total of 37 IT and other local U.S. government officials, Norris (2005) found that local governments adopted and implemented online services mostly to provide information and e-services and also to provide citizen access to government officials.…”
Section: Figure 3 External Reasons To Undertake E-services Initiativessupporting
confidence: 77%
“…Based on four focus groups involving a total of 37 IT and other local U.S. government officials, Norris (2005) found that local governments adopted and implemented online services mostly to provide information and e-services and also to provide citizen access to government officials. Moreover, based on a nationwide survey of U.S. local governments in 2011, Norris and Reddick (2013) found the following top six reasons for local governments to provide e-government services: 1) citizen access to local government information, 2) citizen access to the local government, 3) citizen access to elected officials, 4) to save money, 5) citizen access to appointed officials, and 6) citizen participation in government/e-democracy. Furthermore, Norris and Reddick (2013) identified the top 12 impacts or changes felt by local governments, namely improved customer service, improved local government communication with the public, increased efficiency of business processes, increased time demands on IT staff, increased citizen contact with elected and appointed officials, changes in the role of department staff, decreased transaction times, changes in the role of IT staff, re-engineering of business processes, and reduction or increase in time demands on departmental staff and reduced administrative costs.…”
Section: Figure 3 External Reasons To Undertake E-services Initiativesmentioning
confidence: 99%
“…The outcomes demonstrated three compelling factors, execution anticipation, social impact, and encouraging conditions [7] . The study likewise indicated different factors, for example, society, which was excluded in this connection, yet in future studies in view of its significance.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Studies have concluded that population size is one of the main factors impacting on the implementation of e-government initiatives (Holden et al, 2003;Norris and Reddick, 2013). Thus, the larger the population, the greater the pressure on a government to disclose information, and especially by means of the internet (Serrano, Rueda and Portillo, 2009).…”
Section: Local Populationmentioning
confidence: 99%